Viewpoint: Availability of oestrogen receptor and HER2 status for the breast multidisciplinary meeting discussion; time to get it right. Issue 7 (July 2016) - Francis, A.; Bartlett, J.; Rea, D.; Pinder, S.E.; Stein, R.C.; Stobart, H.; Purdie, C.A.; Rakha, E.; Thompson, A.; Shaaban, A.M.
Abstract: The efficacy and pivotal role of the multidisciplinary meeting (MDM) in informed decision making is well established. It aims to provide a forum in which clinical evidence combines with individual patient data to create a personalized treatment plan. It does not fulfil this role adequately when undertaken without the full results of the patient's investigations being available. Neither doctor nor patient can make an informed decision about treatment options without knowledge of the tumour receptor status. Both targeted therapies and the aim to treat a majority of patients within clinical trials must now drive MDM decision making to be based on accuracy and best available treatment choices. A fully informed decision on treatment delayed by 1–2 weeks is clearly preferable to rushed time target-driven decisions made without the patient being offered a fully informed choice as ratified by a multidisciplinary team. Whilst the early anxiety of waiting for all relevant information to be available may be stressful for patients, not being sure that they have been offered fully informed treatment choices is also stressful and could cause longer lasting anxiety both during and after treatment. MDMs need to develop (along with targeted therapies) to retain their role as a forum whereby patients receive a correct, but specifically a full diagnosis and allow a fully informed discussion of all treatment options, including pre-operative clinical trials.